2008
DOI: 10.1093/chromsci/46.9.813
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ketoprofen and Mefenamic Acid by High- Performance Liquid Chromatography with Molecularly Imprinted Polymer as the Stationary Phase

Abstract: A simple and sensitive high-performance liquid chromatographic method for simultaneous determination of ketoprofen and mefenamic acid in tablets has been developed. HPLC with UV detection (220 nm) was performed on an analytical column packed with molecularly imprinted polymer (MIP) as the stationary phase. The MIPs are prepared by bulk polymerisation followed by crushing and sieving to the desired particle size. In this paper, we selected ketoprofen, methacrylic acid, and ethylene glycoldimethacrylate as templ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Ketoprofen quantification was performed by UV spectrophotometry with a Schimadzu UV-2401 PC spectrophotometer (Kyoto, Japan) at 260 nm (see Figure S2 in supporting information). A previous study has indeed shown that, given the extremely low values of the Ketoprofen limits of quantification (LOQ, 0.122 µg/mL) and detection (LOD, 0.244 µg/mL) with a similar spectrophotometer as the one used in this study (Zafar et al, 2013), this method is appropriate to measure the concentration of Ketoprofen in the release medium (Hung and Hwang, 2008). A calibration curve was first obtained by plotting different known concentrations of Ketoprofen as a function of the peak intensity at 260 nm (see Figure S3 in supporting information).…”
Section: Physicochemical and Encapsulation Properties Of Drug-loaded ...mentioning
confidence: 85%
“…Ketoprofen quantification was performed by UV spectrophotometry with a Schimadzu UV-2401 PC spectrophotometer (Kyoto, Japan) at 260 nm (see Figure S2 in supporting information). A previous study has indeed shown that, given the extremely low values of the Ketoprofen limits of quantification (LOQ, 0.122 µg/mL) and detection (LOD, 0.244 µg/mL) with a similar spectrophotometer as the one used in this study (Zafar et al, 2013), this method is appropriate to measure the concentration of Ketoprofen in the release medium (Hung and Hwang, 2008). A calibration curve was first obtained by plotting different known concentrations of Ketoprofen as a function of the peak intensity at 260 nm (see Figure S3 in supporting information).…”
Section: Physicochemical and Encapsulation Properties Of Drug-loaded ...mentioning
confidence: 85%
“…Efforts to employ MIPs in assays have extended well beyond the large volume of literature focused upon MIPSE, most notably CE and CEC, and LC . In contrast to the 1990s and early 2000s, the proportion of studies devoted to, or heavily dependent upon, LC has reduced significantly.…”
Section: Applicationsmentioning
confidence: 99%
“…Various methods have been reported for the determination of mefenamic acid as pure and in dosages forms. These methods include titrimetric [9,10], chromatographic [11][12], luminescence [13], flow injection [14][15], electrometric [16], spectroflourometric [17][18] and spectrophotometric methods [19][20][21][22].…”
Section: Open Accessmentioning
confidence: 99%